Project GENESIS: An All-inclusive Model to Perform Cost-Benefit Analysis of Green Roofs and Walls - Matos Silva, Cristina; Oliveira Cruz, Carlos; Teotónio, Inês (European Journal of Sustainable Development, 2019)
Green roofs and walls are one of the most promising alternatives for retrofitting existing built environments and tackle urban challenges in a multifunctional way. Yet, these solutions are being confined to specific countries or cities, as their economic contribution has not been fully examined nor accepted. GENESIS is a trans-disciplinary project funded by FCT - Fundação para a Ciência e a Tecnologia that will develop a systematic and comprehensive model to support potential investors or decision-makers, balancing the costs with the benefits of green roofs and walls in a life cycle perspective. The main objective of the project is to enhance existing cost-benefit analysis of green roofs and walls through a multidisciplinary approach that will allow the replication in different regions and type of infrastructures. This will be achieved by: i) monetizing and including all economic, social and environmental benefits in the analysis in order to weight different types of benefits (even those that are typically difficult to estimate because they have no market value) and establish a comparative basis of alternative solutions and potential scenarios; ii) comprising an uncertainty model to cope with climate change and inaccurate forecasting of benefits/costs modelling and; iii) including multi-criteria mode in order to incorporate users and investors preferences. This all-inclusive model crucial for a wide spreading in is green roofs and walls and a more sustainable development in cities. Keywords: green roofs/walls; cost-benefit analysis; investors/users preferences; sustainable urban development; uncertainty